In vitro Viscosity as a Function of Guar Meal and ß-Mannanase Content of Feeds - Lee, Jason T.; Bailey, Christopher A.; Cartwright, Aubrey L. (International Journal of Poultry Science, 2009)
Guar meal, a high protein by-product of guar gum production can be separated into germ and hull fractions. Guar meal at high concentrations in the diet depresses growth and feed efficiency of chickens. The gum, a galactomannan polysaccharide increases intestinal viscosity and thereby decreases nutrient absorption. Guar gum residue is the presumptive anti-nutritive factor in guar meal. An in vitro procedure was developed to measure the impact of guar meals and endo-ß-mannanase (Hemicell®) on feed viscosity. ß-mannanase was added to diets containing 0, 2.5, 5.0, 7.5 and 10.0% germ and hull guar meal fractions. ß-mannanase was added into each diet at ten different concentrations ranging from 1/32-100 times the recommended dose (1.09 x 105 units/kg). Feed samples were mixed with water and enzyme solution (1:5 w/v) and incubated. Subsequently, samples were centrifuged and supernatant viscosity measured. Supernatant viscosity increased in direct proportion to guar meal concentration. Hull fraction increased viscosity more than the germ fraction. ß-mannanase significantly reduced the viscosity of all diets except the 2.5% germ fraction diet. An inverse relationship was observed between enzyme concentration and sample viscosity from 0 to the recommended enzyme level. Enzyme concentrations exceeding the recommended level did not further reduce viscosity of feed supernatant. These results are consistent with feed viscosity as the basis of feed efficiency improvement with enzyme feeding. Increased viscosity with guar meal inclusion and reduced viscosity with enzyme inclusion is consistent with the hypothesis that feed viscosity is the anti-nutritive effect of guar meal feeding.